Analisis Strategi Perlawanan Indonesia Dalam Diskriminasi Kelapa Sawit Oleh Uni Eropa - M Fuadillah Nugraha (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2021)
This study aims to determine how Indonesia's resistance strategy in oil palm discrimination by the European Union. Researchers use the perspective of liberalism and idealism, and the basic assumptions are peace and war avoidance. The results show that EU discrimination against Indonesian CPO products requires players in the palm oil industry and the Indonesian government to work together to design and develop intensive diplomatic efforts aimed at the EU government and its people. The Indonesian government's efforts to oppose the EU's incentives for the use of palm oil are 1) filing claims and challenges against the EU incentives to reject palm oil restrictions, 2) The Indonesian government emphasizes the importance of distributing Indonesian palm oil globally 3) Lobbying the leadership of the APEC organization to ensure the safety of Indonesia's palm oil industry 4) Undertake Join Capaign efforts by the world's largest palm oil producer to protect the stability of palm oil shipments and take action against negative campaigns against palm oil, and unite voices in drafting an agreement to jointly support industrial development palm oil to be more resilient against the global backlash on palm oil.